THE ROLE OF EMPLOYEE PERFORMANCE AFFECTING THE WORK ENVIRONMENT AND LEADERSHIP - Elfi Azhar (CERED Indonesia Institute, 2021)
Employee performance is one of the important aspects in the organization, in addition to achieving goals optimally and can make a positive contribution to the development of employees in the world of work. Employee performance is influenced by many factors such as leadership, work environment, career development, skills, motivation and work environment. This study does not consider all factors, but only focuses on leadership style and work environment. The purpose of this study is to identify and analyze the impact of leadership on employee performance, identify and analyze the impact of the workplace on employee performance, and determine the impact of leadership and workplace on employee performance. PDAM Tirtanadi employee, North Sumatra. This study uses the theory of human resources related to leadership, work environment and employee performance. The approach used in this study is an associative approach. The population of this study is entirely dependent on PDAM Tirtanadi, North Sumatra, as many as 265 people, but the sample that meets the criteria for taking observation samples is 158 people using the Slovenian formula. The method of data collection in this study used the questionnaire method. The data analysis technique in this study uses classical hypothesis testing, multiple regression, hypothesis testing (t-test and F-test), and determinants. Data processing in this study used the Social Science Statistics Package (SPSS) version 2.00. Partially,Leadership is known to have a positive and significant effect on employee performance at the PDAM head office in Tirtanadhi, North Sumatra. In part, the work environment is known to have a positive and significant effect on employee performance at the PDAM head office in Tirtanadhi, North Sumatra. Meanwhile, leadership and working conditions are known to have a significant positive effect on employee performance at the head office of PDAM Tirtanadi, North Sumatra.